2017
DOI: 10.1016/j.annepidem.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Associations between neighborhood characteristics and sexual risk behaviors among HIV-infected and HIV-uninfected women in the southern United States

Abstract: Introduction Neighborhood characteristics shape sexual risk in HIV-uninfected adults in the United States (US). We assess relationships between census tract characteristics and sexual risk behaviors in a predominantly HIV-infected cohort of women living in the Southern US. Methods This cross-sectional multilevel analysis included data from 737 HIV-infected and HIV-uninfected women enrolled in the Women’s Interagency HIV Study. Administrative data captured characteristics of census tracts where women lived; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…For example, neighborhood measures of the material economic environment might be related to access to resources, which could in turn possibly affect diet and other behaviors associated with microbiome composition ( 24 ). Similarly, neighborhood measures of social capital might reflect the social network, which could subsequently impact social support, norms and beliefs around hygiene practices, and sexual activity ( 25 27 ). Likewise, neighborhood measures of stressful or violent environments might be correlated with psychosocial health, which could also influence microbiome composition ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, neighborhood measures of the material economic environment might be related to access to resources, which could in turn possibly affect diet and other behaviors associated with microbiome composition ( 24 ). Similarly, neighborhood measures of social capital might reflect the social network, which could subsequently impact social support, norms and beliefs around hygiene practices, and sexual activity ( 25 27 ). Likewise, neighborhood measures of stressful or violent environments might be correlated with psychosocial health, which could also influence microbiome composition ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies examined the relationship between objective measures of neighborhood-level factors and sexual risks behavior. Living in a more disadvantaged neighborhood was associated with inconsistent condom use [ 25 , 56 , 57 ]. However, findings regarding anal intercourse were mixed as one study identified an inverse relationship between neighborhood condition and anal sex [ 34 ] while another detected a direct relationship [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Living in a more disadvantaged neighborhood was associated with inconsistent condom use [ 25 , 56 , 57 ]. However, findings regarding anal intercourse were mixed as one study identified an inverse relationship between neighborhood condition and anal sex [ 34 ] while another detected a direct relationship [ 57 ]. Young MSM in neighborhoods with greater disadvantage (e.g., percentage of households in poverty) were less likely to report serodiscordant partners [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with Jiang et al (2018) who showed that new infections occurred in people with homosexual behavior or causal sex partners. Haley et al (2017) showed that there was sexual intercourse without a condom (OR= 0.49) on HIV status.…”
Section: The Effect Of Sexual Behavior On Hiv Statusmentioning
confidence: 99%